Structural dynamics of human fatty acid synthase in the condensing cycle - Wooyoung Choi; Chengmin Li; Yifei Chen; YongQiang Wang; Yifan Cheng (Nature, 2025)
Abstract Long-chain fatty acids are the building blocks of fat in human bodies. In mammals, fatty acid synthase (FASN) contains multiple enzymatic domains to catalyse all chemical reactions needed for de novo fatty acid synthesis1. Although the chemical reactions carried out by these enzymatic domains are well defined, how the dimeric FASN with an open architecture continuously catalyses such reactions to synthesize a complete fatty acid remains elusive. Here, using a strategy of tagging and purifying endogenous FASN in HEK293T cells for single-particle cryo-electron microscopy studies, we characterized the structural dynamics of endogenous human FASN. We captured conformational snapshots of various functional substates in the condensing cycle and developed a procedure to analyse the particle distribution landscape of FASN with different orientations between its condensing and modifying wings. Together, our findings reveal that FASN function does not require a large rotational motion between its two main functional domains during the condensing cycle, and that the catalytic reactions in the condensing cycle carried out by the two monomers are unsynchronized. Our data thus provide a new composite view of FASN dynamics during the fatty acid synthesis condensing cycle.